2013
DOI: 10.1007/s10295-013-1329-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cell growth and l-lysine production by genetically modified Corynebacterium glutamicum during growth on molasses

Abstract: Fructose-1,6-bisphosphatase (FBPase) and fructokinase (ScrK) have important roles in regenerating glucose-6-phosphate in the pentose phosphate pathway (PPP), and thus increasing L-lysine production. This article focuses on the development of L-lysine high-producing strains by heterologous expression of FBPase gene fbp and ScrK gene scrK in C. glutamicum lysC (fbr) with molasses as the sole carbon source. Heterologous expression of fbp and scrK lead to a decrease of residual sugar in fermentation broth, and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The rates of sugar consumption, biomass growth, and L-lysine accumulation in the fermentation of L-lysine using untreated beet molasses were lower, when compared with those observed in L-lysine fermentation using other carbon sources. In previous studies, inefficient conversion of molasses had also been reported in the fermentation of L-lysine [4], pullulan [13], L-lactic acid [5]. However, several reports have proved that pretreatment could improve the fermentable properties of molasses, thereby increasing the sugar consumption rate and target product yield [5,15,[17][18][19].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The rates of sugar consumption, biomass growth, and L-lysine accumulation in the fermentation of L-lysine using untreated beet molasses were lower, when compared with those observed in L-lysine fermentation using other carbon sources. In previous studies, inefficient conversion of molasses had also been reported in the fermentation of L-lysine [4], pullulan [13], L-lactic acid [5]. However, several reports have proved that pretreatment could improve the fermentable properties of molasses, thereby increasing the sugar consumption rate and target product yield [5,15,[17][18][19].…”
Section: Resultsmentioning
confidence: 94%
“…Becker et al [10] and Ahmed et al [1] used metabolically engineered C. glutamicum and B. lactofermentum, respectively, to obtain high L-lysine yield, titer, and productivity only with a mixture of molasses and glucose. Xu et al [4] developed an L-lysine-producing engineered C. glutamicum strain that could utilize molasses (pretreated by filtration to remove suspended components) as a sole carbon source, but this strain still showed a longer lag phase and a slower sugar consumption rate [lower than 1 g/(L h)] in batch cultivation. Several studies have been conducted to develop sucrose-metabolizing E. coli strains using gene recombination technology to produce succinic acid [7], L-lactic acid [11], and benzaldehyde lyase [9] from molasses, the productivities, titer, yield, and biomass achieved using untreated molasses were significantly lower than those obtained using glucose or sucrose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C and shaking at 200 rpm for 72 H. The cells were harvested for enzyme activity analysis and SAM production. The dry cell weight (DCW) per liter of C. glutamicum was calculated according to formula: DCW = 0.34 × OD 562 [36].…”
Section: Methionine Adenosyltransferase Purification From E Coli Bl2mentioning
confidence: 99%
“…In addition, sucrose has also a beneficial effect on protection of cells from oxidative, heat, and acids stresses, so it can be an appropriate carbon source to enhance bioproduct production. Molasses, a waste product of the sugar industry, is widely used for L-lysine (Xu et al 2013) and ethanol (Kopsahelis et al 2007(Kopsahelis et al , 2009) production by microbial fermentation. Molasses is a mixture of sugar, nonsugars, and water.…”
Section: Introductionmentioning
confidence: 99%